The Influence of Perceived Ease of Use and Convenience on the Decision to Use QRIS among Students of the Faculty of Economics and Business, University of Mataram - Vrannya Swartitha Ray; Alamsyah AB (LP2M IAIN Palopo, 2026)
The development of digital payment technology in Indonesia is rapid, with QRIS transactions reaching IDR 266 trillion in 2024, but its application is still limited among students despite high awareness. This study aims to analyze the influence of perceived ease of use and convenience on the decision to use QRIS among students of the Faculty of Economics and Business, University of Mataram partially and simultaneously. The type of associative quantitative research with multiple linear regression analysis using SPSS 26. The population of 3,934 active students, a sample of 100 people was selected purposively with the Slovin formula (e = 10%) who had used QRIS. The Likert scale questionnaire instrument (36 items) was validated, analyzed using classical assumption tests (normality, multicollinearity, heteroscedasticity). The results showed that perceived ease of use (β = 0.219, t = 2.442, Sig = 0.016) and convenience (β = 0.675, t = 6.499, Sig = 0.000) had a significant effect partially; F=135.456 (Sig=0.000), explaining 73.6% of the variance (R²=0.736). In conclusion, the second factor driving QRIS implementation suggests optimizing user-friendly design for stakeholders, even though it is limited to one faculty.​